An Evaluation of Credit Risk Management in the Polish Banking Sector - Kuchciak, Iwa (Efekty zarządzania ryzykiem kredytowym w polskim sektorze bankowym, 2011)
Polish banks have been affected by the repercussions of the financial crisis so they have to respond to new market conditions by changing the risk management style. The aim of this paper is to present the challenges in credit risk management facing the Polish banking sector now. This paper deals with one of the strongest kinds of risk affecting Polish banks. The attention will be focused on the factors responsible for an increase in credit risk in the Polish banking sector and its influence on the financial results achieved by banks.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 230-241
Keywords: Polish banking sector; credit risk; management of credit risk; loans quality